Design of library application system - ., Wulandari; Aminin, Sudirman; Ihsan Dacholfany, M.; Mujib, Abdul; Huda, Miftachul; Mohd. Nasir, Badlihisham; Maseleno, Andino; Sundari, Eni; ., Fauzi; Masrur, M. (International Journal of Engineering and Technology, 2018)
Library application is a computer program designed specifically to manage the data of borrowing and returning books in order to be presented more quickly. In addition, for the achievement of the purpose of the operation itself is to facilitate students by providing facilities. In making this application there were some important data such as Member data, Books, Transactions, and Admin. From the data were expected to be the basis made for this application in order to present the information needed quickly and precisely, and to improve the performance of librarians. Requirements as a member of the library is a Student of SMP Negeri 1 Talangpadang, then create a regis                                                                                                                                                                                                                                                                                                                                                                                     tration form to become a member of SMP Negeri 1 Talangpadang Students. The expected result of making this system was that the data that had been stored and managed manually can begin to be computerized so as to further advance the performance and facilitate librari-ans in carrying out activities related to the library itself.